Effects of processing parameter on phase transition and electrical properties of lead-free BNKT piezoelectric ceramics - Pichitchai Butnoi (2018)
© 2017 Taylor & Francis Group, LLC. Lead-free piezoelectric ceramics of Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 powders were prepared via a conventional solid-state reaction method, and effects of calcination temperature on many properties of the ceramics were investigated. XRD patterns for all ceramic samples showed coexistence between rhombohedral and tetragonal phases without any impurity. Calcination temperatures from 700 to 1000°C shifted depolarization temperature from 92 to 100°C. Dielectric and piezoelectric properties were improved and showed the optimum values for the ceramics which calcined at 800°C. The improvements of piezoelectric properties were related with the ceramic densification and MPB composition.